About borders and their movement in spaces of contemporary art - Pankowska, Krystyna (Granice tolerancji w sztuce i w wychowaniu, 2020)
For a long time, artists have pushed aesthetic and ethical boundaries, making them ahead of their time and constituting their sensitive seismograph. Since art is an expression of its times, the question arises what and how does contemporary art express, which in a controversial and violent way shifts and expands its boundaries. The phenomenon of destabilization of boundaries (ethical, aesthetic) was decreed by postmodernism, the shortest definition of which is: everything is allowed. The methodological correctness of postmodernism assumed that no limits could be set, nothing could be hierarchized, nothing could be set on the scale of inferiority and superiority. The purpose of this text is to show, on selected examples, that artists go beyond the socially accepted framework of creativity, including those concerning the taking up of previously absent topics or the use of new matter and means of expression in constructing artistic statements. The text is an attempt to show changes in art as phenomenon resulting from changes in other dimensions of our reality, liberated from earlier socially accepted norms and aesthetic fetters.